THE IMPLEMENTATION OF ENGLISH LESSON MATERIAL SOURCE FROM THE RUMAH BELAJAR PORTAL IN TEACHING ENGLISH - Azwar Azwar; Rafi’ah Nur; Siti Hajar (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Knowledge of English is very important nowadays. in the world of education, a teacher must be creative in choosing teaching materials. Therefore, this must be supported by the skills of the teacher and the suitability of the media in teaching. The purpose of this research is to find out whether the use of the learning house application can make it easier for teachers and increase students' interest. Rumah Belajar portal is a medium that can help teachers and students in the teaching and learning processThe data collection technique in this study is the process of collecting and processing information to evaluate results and use them for research. The research sample consisted of 20 students from eight grade. The results of the analysis The application of English learning material sources from the Rumah Belajar portal is very helpful for teachers in teaching English at SMP Satap 8 Baraka. This can be seen from the results of observations and interviews. The observation results show that teachers are successful in their performance to present their material, have a good influence on influencing students to follow their instructions, create good communication during sharing time, and make the class active. In addition, the results of the interviews showed that the teacher gave positive comments on the implementation of English subject matter sourced from The Rumah Belajar portal.